Bimetal / molecular sieve composite catalyst and preparation method thereof
By synthesizing bimetallic PtCe catalyst on ZSM-5 molecular sieve support, and using CeO2 to regulate the redox properties of Pt, the problem of sintering and aggregation of active sites of noble metal catalysts is solved, the catalytic performance and stability are improved, and efficient VOCs removal is achieved.
Patent Information
- Application Number
- CN202411609090.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, noble metal catalysts have problems of sintering and aggregation of active sites during catalytic oxidation of VOCs, which affects the catalytic effect, and there are few researches on molecular sieve support.
A bimetallic PtCe/ZSM-5 catalyst was synthesized by a simple method, and the noble metal Pt was dispersed with a high specific surface area ZSM-5 molecular sieve as a support, and the redox properties of Pt were regulated through CeO2 to improve catalytic performance and stability.
The local structure and chemical properties of precious metal Pt are controlled, the catalytic performance, utilization rate and water resistance stability of catalytic oxidation are improved, and the economic cost of the catalyst is significantly reduced.
Smart Images

Figure CN119608223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental catalysis, and relates to the application of metal / molecular sieve materials in catalytic oxidation of toluene, and in particular to a bimetallic / molecular sieve composite catalyst and a preparation method thereof, and the application of the bimetallic / molecular sieve composite catalyst in catalytic oxidation of VOCs. Background Art
[0002] Volatile organic compounds (VOCs) refer to a class of organic compounds with a boiling point in the range of 50°C to 260°C at normal temperature and pressure, including a variety of types from simple alkanes to complex polycyclic aromatic hydrocarbons. They have a wide range of sources and exist in many industries such as industrial processing, transportation, and building decoration. They are highly volatile and highly toxic, causing serious harm to human health and the natural environment. Therefore, the efficient control of VOCs has become one of the research hotspots in today's society. Catalytic oxidation technology is one of the technologies currently widely used at home and abroad to control VOCs. It can directly convert pollutants into CO2 and H2O, with high elimination efficiency, no secondary pollution, and environmental friendliness. The development of efficient VOCs catalysts is the key to realizing catalytic oxidation technology.
[0003] The catalysts commonly used in catalytic oxidation technology mainly include supported precious metal catalysts and transition metal oxides. Among them, although precious metal catalysts are more expensive, they are often the first choice for catalytic oxidation of VOCs due to their excellent activity. Precious metal phases are often supported by metal oxides, graphene, MOFs materials and molecular sieves. Among them, molecular sieves are ideal carriers for metal catalysts due to their large specific surface area, moderate surface acidity, good active site dispersion, hydrothermal stability, and adsorption and catalytic dual functionalization. For supported precious metal catalysts, the dispersion, size and stability of the precious metal on the carrier are crucial to the catalytic performance. Therefore, the development of efficient and economical technologies to improve the activity, utilization and stability of precious metals remains a research hotspot in this field.
[0004] Commonly used noble metal catalysts include Pd, Pt, Au and Ag. It is generally believed that the order of activity in the catalytic oxidation of toluene is Pt>Pd>Au>Ag. Pt-based catalysts usually show better catalytic performance, but their active sites are easily sintered and agglomerated at high temperatures, which affects the catalytic effect. Transition metal oxides are less effective than noble metals when used as catalytic oxidation catalysts alone. They are often added to noble metal-based materials as promoters to adjust the structure and properties of noble metals, improve the catalytic activity and stability of noble metal-based catalysts, and reduce economic costs. Among these transition metal oxides, CeO2 has abundant oxygen vacancies and unique properties of storing and releasing oxygen (redox properties), which is helpful for the redox of loaded noble metals. Abbasi et al. successfully synthesized Pt / Al2O3-CeO2 nanostructured catalysts by impregnation method (reference Synthesis and physicochemical characterizations of nanostructured Pt / Al2O3–CeO2 catalysts for total oxidation of VOCs). The study found that due to the presence of Pt as an active compound and CeO2 as an additive, Pt on Al2O3-supported CeO2 is highly reducible, can completely degrade toluene at 250°C, and has a high removal efficiency for BTX at different concentrations and WHSV. Shi et al. synthesized Pt / CeO2-TiO2 catalysts with different Ce / Ti molar ratios. By adjusting the Ce / Ti molar ratio, highly dispersed Pt species can be obtained. The strong interaction between highly dispersed Pt species and CeO2-TiO2 and the formation of more Ce2Ti2O7 species promote the migration of lattice oxygen, so that the Pt / CeO2-TiO2 catalyst has more active Pt species, adsorbed oxygen species and higher low-temperature reducibility, which promotes the catalytic activity for a variety of VOCs models (n-hexane, benzene, ethyl acetate, acetonitrile and 1,2-dichloroethane) (reference New insight into the design of highlydispersed Pt supported CeO2–TiO2 catalysts with superior activity for VOCslow-temperature removal). However, current research on the use of CeO2 promoters to regulate precious metal-based materials is mainly focused on metal oxide supports, and relatively little research is related to molecular sieve supports.
[0005] A series of progress has been made in using CeO2 promoters to improve the activity and stability of precious metal-based materials, and they have been applied in the fields of methane oxidation, conversion of hydrogen storage compounds, biomass conversion, selective hydrogenation, photocatalysis, etc. However, current research on the catalytic degradation of VOCs is mainly focused on metal oxide supports, and there is relatively little research on molecular sieve supports. Traditional oxides usually have relatively low specific surface areas and random pores, which significantly affect the catalytic conversion of VOCs. In contrast, the high specific surface area, ordered pores, and adsorption and catalytic dual functionalization of molecular sieve supports can effectively improve the catalytic oxidation efficiency. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a bimetallic / molecular sieve composite catalyst and its preparation method and application in catalytic oxidation of VOCs. The present invention adopts a simple method to synthesize a bimetallic PtCe / ZSM-5 catalyst, uses a high specific surface area ZSM-5 molecular sieve as a carrier to disperse the precious metal Pt, and uses CeO2 with unique redox properties to regulate Pt, thereby improving the catalytic performance, utilization rate and water resistance stability of the precious metal Pt for toluene.
[0007] The bimetallic PtCe / ZSM-5 catalyst developed by the present invention can achieve regulation of the local structure and chemical properties of the noble metal Pt, thereby improving its catalytic performance, utilization rate and water resistance stability in catalytic oxidation of toluene.
[0008] The technical solution of the present invention is:
[0009] A bimetallic / molecular sieve composite catalyst, characterized in that the loading content of the first metal platinum accounts for 1wt% of the molecular sieve solid content, and the loading content of the second metal accounts for 0wt% to 1wt% of the molecular sieve solid content.
[0010] Furthermore, the second metal is Ce, Mn, Cu, Cr or Co, and the molecular sieve is ZSM-5, NaY, Beta, Y or MWW.
[0011] A preparation method of a bimetallic / molecular sieve composite catalyst comprises the following steps: firstly, co-impregnating chloroplatinic acid, a metal salt and a molecular sieve, and then drying and calcining the co-impregnated solution to obtain the bimetallic / molecular sieve composite catalyst; wherein, platinum is used as a first metal and its loading content is fixed to 1wt% of the molecular sieve solid content, and the metal in the metal salt is used as a second metal and its loading content is adjusted to obtain a bimetallic / molecular sieve composite catalyst with different second metal loading contents.
[0012] Furthermore, the second metal is Ce, and the metal salt is CeN4O 12The loading content of the second metal Ce in the bimetallic / molecular sieve composite catalyst accounts for 0wt% to 1wt% of the molecular sieve solid content.
[0013] Furthermore, the second metal is Mn, Cu, Cr or Co.
[0014] Furthermore, the molecular sieve is NaY, Beta, Y or MWW.
[0015] Furthermore, the molecular sieve is ZSM-5, and the bimetallic / molecular sieve composite catalyst is a PtCe / ZSM-5 catalyst.
[0016] Further, the method for preparing a bimetallic / molecular sieve composite catalyst having a Ce content of 0.6 wt% is as follows:
[0017] 1) 0.0166g CeN4O 12 Add 1.891 mL of 0.0111 g / mL H2PtCl6 aqueous solution, stir evenly, add molecular sieves, stir again for 12 h, and dry at 110 °C overnight;
[0018] 2) The solid product obtained in step 1) is calcined in a muffle furnace at 550° C. for 6 h to obtain a bimetallic / molecular sieve composite catalyst.
[0019] Furthermore, the molecular sieve is 1 g of dried ZSM-5.
[0020] An application of the bimetallic / molecular sieve composite catalyst for catalytic oxidation of VOCs.
[0021] The advantages of the present invention are as follows:
[0022] Based on the catalytic oxidation method with lower energy consumption and higher efficiency, a metal / molecular sieve composite catalyst with high activity and stability has been developed to further achieve the efficient removal of VOCs pollutants.
[0023] Develop simple methods to regulate the local structure and chemical properties of precious metals, and further improve the catalytic performance, utilization and stability of precious metals.
[0024] The present invention develops a noble metal-transition metal / molecular sieve composite catalyst by a simple method, reduces the economic cost of the catalyst, and improves the catalytic activity, utilization rate and water resistance stability of the noble metal-based material in catalytic oxidation of toluene. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a flow chart of the preparation method.
[0026] Figure 2This is a graph showing the research results of catalytic oxidation of toluene by PtCe / ZSM-5;
[0027] (a) Catalytic performance of Pt / ZSM-5 and PtCe / ZSM-5, (b) Ce content and T 90 Relationship diagram, (c) catalytic oxidation performance diagram of 0.6Ce / ZSM-5.
[0028] Figure 3 This is a graph showing the research results on the stability and water resistance of PtCe / ZSM-5;
[0029] (a) Long-period performance diagram of Pt0.6Ce / ZSM-5, (b) Water-resistance performance diagram of Pt / ZSM-5, (c) Water-resistance performance diagram of Pt0.6Ce / ZSM-5. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention but not to limit the scope of the present invention.
[0031] The preparation process of the present invention is as follows Figure 1 As shown, chloroplatinic acid H2PtCl6, cerium (IV) nitrate CeN4O 12 The co-impregnation was carried out with molecular sieves, the Pt loading content was fixed at 1wt%, and the Ce loading content was adjusted (0wt%, 0.1wt%, 0.3wt%, 0.6wt%, 0.85wt%, 1wt%). The co-impregnation solution was dried and calcined to obtain PtCe / ZSM-5 catalysts with different Ce loading contents, and catalytic oxidation reaction was carried out with toluene under certain conditions to investigate the catalytic activity, stability and water resistance of PtCe / ZSM-5. The loading contents of Pt and Ce are relative to the solid content of the added molecular sieve.
[0032] Technical Solution
[0033] 1) Preparation of PtCe / ZSM-5: (taking Pt0.6Ce / ZSM-5 as an example)
[0034] Weigh 0.0166g CeN4O 12 , added to 1.891mL of H2PtCl6 (0.0111g / mL) aqueous solution, stirred evenly, added 1g of dried ZSM-5 molecular sieve, stirred thoroughly for 12h, and the sample was dried at 110℃ overnight. Finally, the solid product was calcined in a muffle furnace at 550℃ for 6h, and the obtained sample was named Pt0.6Ce / ZSM-5. Changing CeN4O 12 The above operation was repeated with the addition amount to obtain other samples with different Ce contents.
[0035] CeN4O during calcination12 It will become the regulation of Pt by CeO2; by changing the content of cerium Ce, bimetallic catalysts with different performances can be obtained, and when the cerium Ce content is 0.6wt%, the optimal catalytic performance is achieved, which is better than the single metal catalyst loaded with pure Pt.
[0036] 2) Study on the catalytic oxidation of toluene by PtCe / ZSM-5:
[0037] Taking toluene (a type of VOCs) as an example, a micro-normal pressure fixed bed catalytic reaction device was used to test the catalytic oxidation performance of the catalyst on toluene. The test steps are as follows: first, 0.2g PtCe / ZSM-5 catalyst (20-40 mesh) was prepared, and it was purged and reduced at 350°C for 1h under a H2 / Ar mixed gas containing 10% H2 by volume, and then the 0.2g catalyst (20-40 mesh) after reduction treatment was loaded into a fixed bed reactor, and then the toluene solution was placed in a constant temperature water bath at 25°C, and a raw gas with a toluene concentration of 1000ppm was generated by passing 20mL / min O2 and 30mL / min N2. After mixing evenly, the raw gas was injected into the fixed bed reactor through a double plunger pump, and the reaction space velocity was maintained at 15000mL / (g cat ·h); finally, the toluene concentration after the reaction was detected by gas chromatography. The catalytic performance of the catalyst on toluene was investigated by setting the temperature of the fixed bed reactor, and the conversion rate at different temperatures was calculated according to the toluene inlet and outlet concentrations. 90 (the temperature corresponding to 90% toluene conversion) was used as the standard to judge the catalytic oxidation performance. The results show that the appropriate amount of Ce loading can significantly improve the catalytic performance. The T of Pt0.6Ce / ZSM-5 90 As low as 158℃, 17℃ lower than that of pure Pt-loaded Pt / ZSM-5. Figure 2 shown.
[0038] 3) Study on the stability and water resistance of PtCe / ZSM-5:
[0039] The stability and water resistance of the catalyst are still tested using the above-mentioned fixed bed catalytic reaction device.
[0040] Stability test steps: After the sample is purged and reduced, it is loaded into a fixed bed reactor, and the temperature of the fixed bed reactor is set to the temperature corresponding to the sample's 100% conversion rate. Other conditions are kept consistent with the performance test conditions, and long-term continuous testing is performed. The test results show that the Pt0.6Ce / ZSM-5 sample can maintain a 100% conversion rate for 120 hours, indicating excellent stability. Figure 3 (a) shown.
[0041] Water resistance test steps: After the sample is purged and reduced, it is loaded into a fixed bed reactor. The temperature of the fixed bed reactor is set to the temperature corresponding to 100% conversion rate of the sample, and other conditions are kept consistent with the performance test conditions. The reaction is allowed to stabilize under dry gas conditions, and then 5 vol% of water vapor is introduced to mix with the raw gas and injected into the fixed bed reactor. After the reaction is stable, the water vapor is turned off, and the test is terminated after stabilization for a period of time. The test results show that Pt0.6Ce / ZSM-5 has excellent water resistance. In the presence of 5 vol% water vapor, it can basically maintain a 100% conversion rate, while Pt / ZSM-5 decreases by 10%, which is greatly affected by water vapor. Figure 3 (b) Figure 3 (c) as shown.
[0042] The control of Pt in this scheme is not limited to Ce, but can also be extended to other transition metals (such as Mn, Cu, Cr, Co, etc., whose loading content accounts for 0wt% to 1wt% of the molecular sieve solid content), using the metal salt of the corresponding transition metal (i.e., the second metal) to replace CeN4O 12 The choice of carrier is not limited to ZSM-5, but can be extended to other molecular sieves (such as Beta, Y, MWW, etc.).
[0043] Although the specific embodiments of the present invention are disclosed for the purpose of illustration, the purpose is to help understand the content of the present invention and implement it accordingly, those skilled in the art will understand that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the present invention should not be limited to the content disclosed in the best embodiment, and the scope of the present invention is subject to the scope defined in the claims.
Claims
1. A bimetallic / molecular sieve composite catalyst, characterized in that: The loading content of the first metal platinum accounts for 1 wt% of the molecular sieve solid content, and the loading content of the second metal accounts for 0 wt% to 1 wt% of the molecular sieve solid content.
2. The bimetallic / molecular sieve composite catalyst according to claim 1, characterized in that: The second metal is Ce, Mn, Cu, Cr or Co, and the molecular sieve is ZSM-5, NaY, Beta, Y or MWW.
3. A method for preparing a bimetallic / molecular sieve composite catalyst, comprising the steps of: First, chloroplatinic acid, metal salt and molecular sieve are co-impregnated, and then the co-impregnated solution is dried and calcined to obtain a bimetallic / molecular sieve composite catalyst; wherein platinum is used as the first metal and its loading content is fixed to 1wt% of the molecular sieve solid content, and the metal in the metal salt is used as the second metal and its loading content is adjusted to obtain a bimetallic / molecular sieve composite catalyst with different second metal loading contents.
4. The method according to claim 3, characterized in that The second metal is Ce, and the metal salt is CeN4O 12 The loading content of the second metal Ce in the bimetallic / molecular sieve composite catalyst accounts for 0wt% to 1wt% of the molecular sieve solid content.
5. The method according to claim 3, characterized in that: The second metal is Mn, Cu, Cr or Co.
6. The method according to claim 3, characterized in that The molecular sieve is NaY, Beta, Y or MWW.
7. The method according to claim 3, characterized in that The molecular sieve is ZSM-5, and the bimetallic / molecular sieve composite catalyst is a PtCe / ZSM-5 catalyst.
8. The method according to claim 3, characterized in that The method for preparing a bimetallic / molecular sieve composite catalyst having a Ce content of 0.6 wt% is as follows: 1) 0.0166g CeN4O 12 Add 1.891 mL of 0.0111 g / mL H2PtCl6 aqueous solution, stir evenly, add molecular sieves, stir again for 12 h, and dry at 110 °C overnight; 2) The solid product obtained in step 1) is calcined in a muffle furnace at 550° C. for 6 h to obtain a bimetallic / molecular sieve composite catalyst.
9. The method according to claim 8, characterized in that The molecular sieve is 1g of dried ZSM-5.
10. An application of the bimetallic / molecular sieve composite catalyst according to claim 1 for catalytic oxidation of VOCs.
Citation Information
Cited By
Fly ash-based double-spliced nanosheet SOD zeolite composite catalytic material for ammonia treatment as well as preparation method and application of fly ash-based double-spliced nanosheet SOD zeolite composite catalytic material
CN121016828A